Potential Implications of a Special Safeguard Mechanism in the WTO : The Case of Wheat - Hertel, Thomas W.; Martin, Will; Leister, Amanda M. (2012)
The Special Safeguard Mechanism was a key issue in the July 2008 failure to reach agreement in the World Trade Organization negotiations under the Doha Development Agenda. It includes both price and quantity-triggered measures. This paper uses a stochastic simulation model of the world wheat market to investigate the effects of policy makers implementing policies based on the Special Safeguard Mechanism rules. As expected, implementation of the quantity-triggered measures is found to reduce imports, raise domestic prices, and boost mean domestic production in the Special Safeguard Mechanism regions. However, rather than insulating countries that use it from price volatility, it would actually increase domestic price volatility in developing countries, largely by restricting imports when domestic output is low and prices high. This paper estimates that implementation of the quantity-triggered measures would shrink average wheat imports by nearly 50 percent in some regions, with world wheat trade falling by 4.7 percent. The price measures discriminate against low price exporters -- many of whom are developing countries -- and tend to increase producer price instability.